Differentiating Batrachochytrium dendrobatidis and B. salamandrivorans in Amphibian Chytridiomycosis Using RNAScope®in situ Hybridization - Ossiboff, Robert J.; Towe, Anastasia E.; Brown, Melissa A.; Longo, Ana V.; Lips, Karen R.; Miller, Debra L.; Carter, E. Davis; Gray, Matthew J.; Frasca, Salvatore (Frontiers in Veterinary Science, 2019)
Batrachochytrium dendrobatidis and B. salamandrivorans are important amphibian pathogens responsible for morbidity and mortality in free-ranging and captive frogs, salamanders, and caecilians. While B. dendrobatidis has a widespread global distribution, B. salamandrivorans has only been detected in amphibians in Asia and Europe. Although molecular detection methods for these fungi are well characterized, differentiation of the morphologically similar organisms in the tissues of affected amphibians is incredibly difficult. Moreover, an accurate tool to identify and differentiate Batrachochytrium in affected amphibian tissues is essential for a specific diagnosis of the causative agent in chytridiomycosis cases. To address this need, an automated dual-plex chromogenic RNAScope® in situ hybridization (ISH) assay was developed and characterized for simultaneous detection and differentiation of B. dendrobatidis and B. salamandrivorans. The assay, utilizing double Z target probe pairs designed to hybridize to 28S rRNA sequences, was specific for the identification of both organisms in culture and in formalin-fixed paraffin-embedded amphibian tissues. The assay successfully identified organisms in tissue samples from five salamander and one frog species preserved in formalin for up to 364 days and was sensitive for the detection of Batrachochytrium in animals with qPCR loads as low as 1.1 x 102 zoospores/microliter. ISH staining of B. salamandrivorans also highlighted the infection of dermal cutaneous glands, a feature not observed in amphibian B. dendrobatidis cases and which may play an important role in B. salamandrivorans pathogenesis in salamanders. The developed ISH assay will benefit both amphibian chytridiomycosis surveillance projects and pathogenesis studies by providing a reliable tool for Batrachochytrium differentiation in tissues.